Reading 1-2 Peter and Jude : a resource for students - Mason, Eric Farrel; Martin, Troy W. (Resources for biblical study ;, 2014)
An essential textbook on 1-2 Peter and Jude for readers of all levels Scholars engage the best contemporary work on 1-2 Peter and Jude in this student-oriented book. The first four chapters in this collection-on authorship and pseudonymity, literary relationships among the three books, epistolary rhetoric, and apocalyptic elements-consider important, foundational issues related to all three epistles. These essays lay the groundwork for more focused chapters that examine theology and theory in 1 Peter as well a stylistic, theological, and thematic overlap in Jude and 2 Peter. Features: A range of theological, literary, and theoretical approaches Definitions for specialized terminology Historical and cultural background information Explanations of methodologies.